ПОЛІТИЧНИЙ ДИСКУРС ВЕЛИКОЇ БРИТАНІЇ: КОГНІТИВНИЙ АСПЕКТ - Соколовська, С.В. (Studia Philologica, 2014)
The article deals with the main features of the British political disсourse concerning dominant concepts, metaphorical images, cognitive and speech strategies. Within the framework of the cognitive and discourse paradigm the main contemporary trends and development prospects in the British political discourse researches are defined.